Pemberian Bahan Organic Soil Treatment dan Pupuk Kandang Kotoran Ayam Untuk Perubahan Beberapa sifat Fisik Ultisol - June A Putinella; Andreas Izaac Latupapua (JURNAL PERTANIAN KEPULAUAN, 2022)
Research to determine the effect of OST ingredients and manure from chicken manure on the physical properties of Ultisol was carried out with a completely randomized design with factorial patterns. The experimental treatment consisted of giving OST, namely P0 = without OST, P1 = 5 g/pot, P2 = 10 g/pot combined with manure, B0 = without manure, B1 = 40 g/pot and B2 = 80 g/pot repeated 3 times. The results showed that bulk density, porosity, soil pore distribution and aggregate stability were affected by OST material, while manure only affected aerase pores, unavailable pore water and aggregate stability.